Thiol-Michael 'click' hydrogels as an imageable packing material for cancer therapy. (8th September 2017) - Moon, Nicholas G.; Pekkanen, Allison M.; Long, Timothy E.; Showalter, Timothy N.; Libby, Bruce
Abstract: Gynecological cancer treatment strategies commonly employ pelvic brachytherapy, a technique that temporarily locates radioactive materials in or near the source of the tumor. Despite numerous advances in brachytherapy treatment protocols, advances in the required vaginal packing materials lag significantly. This paper describes a packing material for vaginal brachytherapy based on a poly(ethylene glycol) (PEG)-based hydrogel. Commercially available oligomeric starting materials rapidly formed a hydrogel upon action of mild base (NaHCO3 ) through a thiol-Michael addition reaction. Tuning the base concentration enabled rapid formation of hydrogels with moduli sufficient for effective tissue displacement (>10 kPa). The poly(ethylene glycol) diacrylate oligomer molecular weight exerted minimal influence on the hydrogel modulus. The hydrogels absorbed up to four times their weight in water from the dry state. CT imaging demonstrated distinguishability between hydrogel, water, and metal medical tools. The hydrogels did not induce significant IL-8 upregulation or cytotoxicity when cultured against vaginal macrophage cells, suggesting lack of immunogenicity. Our findings support these hydrogels as ideal candidates for a packing material in pelvic brachytherapy applications. Graphical abstract: Highlights: A PEG-based hydrogel was advanced as a novel packing material for vaginal brachytherapy. Hydrogel formation occurs on a clinically-relevant timescale. Modulus and swelling allowed for potential tissue displacement. Favorable radiation absorption and biocompatibility show potential for immediate clinical application.